(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Dr. Nayyar Parvez, Professor & HOD, Department of Pharmaceutics, School of Pharmacy, Sharda University, Greater Noida, Uttar Pradesh, India Abstract Drug therapy optimization represents the systematic process of maximizing therapeutic benefits while minimizing risks through personalized medication selection and management strategies. Dosing considerations incorporate pharmacokinetic principles, physiological variations, and disease-specific factors requiring individualized adjustment based on renal function, hepatic status, age, weight, and genetic factors affecting drug disposition. Drug interaction management addresses pharmacokinetic and pharmacodynamic mechanisms requiring systematic screening, clinical significance assessment, and mitigation strategies including dose adjustment, spacing administration, or alternative therapy selection. Adverse effect prevention and management employs risk factor identification, proactive monitoring, and intervention protocols balancing therapeutic benefits against potential harms through structured assessment tools and documentation systems. Special population adaptation addresses unique considerations for pediatric, geriatric, pregnant, and physiologically compromised patients requiring specific dosing algorithms, monitoring parameters, and safety precautions. Cost consideration strategies integrate economic factors with clinical decision-making through formulary management, therapeutic interchange, assistance program navigation, and value assessment methodologies. This comprehensive approach ensures patients receive medications optimally matched to their specific needs, characteristics, and circumstances Keywords: Pharmacokinetic Optimization, Patient-Specific Dosing, Polypharmacy Management, Benefit-Risk Assessment, Therapeutic Individualization VIEW PDF